Vaping as a Catalyst for Smoking? An InitialModel on the Initiation of Electronic CigaretteUse and the Transition to Tobacco SmokingAmong Adolescents - Schneider, Sven; Diehl, Katharina (Nicotine & Tobacco Research, 2016)
Introduction: The popularity of electronic cigarettes (e-cigarettes) among adolescents is growingworldwide. A more accurate model than the much discussed but inadequate Gateway Hypothesisis needed to explain some adolescents' initial preference for e-cigarettes over tobacco cigarettes,as well as any transition from e-cigarettes to tobacco smoking. Our aim was to summarize the diffusefear that adolescents will be indirectly encouraged to begin smoking tobacco via the use ofe-cigarettes and to systematize the disparate causal hypotheses used thus far in relevant literature.Methods: We summarized the vague and fragmented hypotheses formulated thus far in literatureon both trajectories from abstinence to e-cigarette use and from there to tobacco smoking into aset of empirically testable hypotheses and organized them into a comprehensive model.Results: Our results indicate that the perceived health risks, specific product characteristics (suchas taste, price and inconspicuous use), and higher levels of acceptance among peers and otherspotentially make e-cigarettes initially more attractive to adolescents than tobacco cigarettes. Later,increasing familiarity with nicotine could lead to the reevaluation of both electronic and tobaccocigarettes and subsequently to a potential transition to tobacco smoking. The suggested "catalystmodel" takes variations in the nicotine content of e-cigarettes as well as the dual use of differentsubstances into account.Conclusion: Our model provides causal hypotheses for the initiation of e-cigarette use and forthe potential transition to tobacco smoking which, after being tested in empirical studies, couldlead to the formulation of concrete recommendations for healthcare intervention and preventionmeasures.Implications: We developed a model that provides causal hypotheses for the initiation of e-cigaretteuse and for the potential transition to tobacco smoking.
CRIS-Team Scopus Importer:2021-12-06